Methyl Donor Nutrient Intake and Risk of Type 2 Diabetes: Results from 3 Large US Cohorts (OR15-02-19). (13th June 2019) - Braun, Kim V E; Satija, Ambika; Voortman, Trudy; Franco, Oscar; Sun, Qi; Hu, Frank; Bhupathiraju, Shilpa
Abstract: Objectives: DNA methylation may play a role in the development of type 2 diabetes (T2D). DNA methylation can be influenced by methyl donor nutrients such as vitamins B2, B6, B12, folate, and methionine, which are all central to one carbon metabolism. Using 3 large cohorts of US health professionals, we examined whether intake of these nutrients from food or supplements is associated with T2D risk. Methods: We included 69, 949 women from the Nurses' Health Study (1984–2012), 90, 239 women from the Nurses' Health Study II (1991–2011), and 40, 539 men from the Health Professionals Follow-Up Study (1986–2010). Dietary data were collected every 2–4 years using a validated semi-quantitative FFQ, from which dietary intakes of vitamin B2, vitamin B6, vitamin B12, folate, and methionine were calculated. We used Cox proportional hazards model with time-varying covariates and adjusted for several sociodemographic and lifestyle variables. We also adjusted for cereal fiber, animal protein, polyunsaturated and saturated fatty acids ratio. Food sources of vitamins were additionally adjusted for multivitamin use while supplemental sources of vitamins were adjusted for a measure of overall diet quality. Results: During 1763, 428 years of follow-up, we documented 8141 T2D cases. In pooled multivariable-adjusted analyses, compared to those in the lowest quintile, those in the highest quintile of vitamins B2 and B6 had a 10% (95% CI 3%–16%) and 11% (95% CI 3%–16%) lower T2D risk, respectively. Total vitamin B12 intake was not associated with T2D. However, when analyses were stratified by source, vitamin B12 from food sources was associated with a higher T2D risk (HR [95% CI] = 1.11 [1.02–1.19]). On the other hand, supplemental vitamin B12 was associated with lower T2D risk (HR [95% CI] for Q5 vs Q1 = 0.92 [0.85–0.98]). We found no evidence for an association between intakes of folate and methionine and T2D risk. Conclusions: Our study suggests that higher intakes of vitamin B2 and vitamin B6 are associated with a lower T2D risk. A higher vitamin B12 intake from food seems to be associated with a higher T2D risk, which may be due to consumption of animal products. Funding Sources: The analysis was supported by grants from the National Institutes of Health.